Creating an ecological trail as a means of formation an culture of the population and preserving rare, protected species of flora. (November 2019) - Popova, E
Abstract: The paper presents an ecological trail created in the area affected by enterprises of the Tobolsk Industrial Site (Tyumen region, Russia). This ecological trail is aimed at preserving old-growth forest areas, creating a vision of harmonious coexistence between a large petrochemical facility and the surrounding natural environment and, therefore, helping to preserve rare, protected and indicator species of the biota identified near the Tobolsk Industrial Site. As a result of the research conducted on the ecological trail, thirteen rare and protected species of flora were identified and preserved. These are: Lobaria pulmonaria L. Hoffm., Phegopteris connectilis (Michx.) Watt., Cystopteris fragilis (L.) Bernh., Dryopteris filix-mas (L.) Schott., Tilia cordata Mill., Calluna vulgaris (L.) Hull., Allium microdictyon Prokh., Neottianthe cucullata L. Schlechter., Malaxis monophyllos L., Dactylorhiza maculata (L.) Soo, Neottia nidus-avis (L.) Rich., Cypripedium guttatum Sw., Listera ovata (L.) R. Br. The area reserved for the ecological trail will be protected from deforestation and construction.